Pengaruh Pendekatan Problem-Driven Iterative Adaptation (PDIA) dan Kepemimpinan Kepala Jurusan terhadap Budaya Disiplin Siswa SMK - Agung Wahono; Ratna Suhartini; Luthfiyah Nurlaela; Rommy Mochamad Ramdhani; I Gusti Putu Asto Buditjahjanto (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – The purpose of this study is to analyze the influence of the Problem-Driven Iterative Adaptation (PDIA) approach and department head leadership on students’ discipline culture in Vocational High Schools, both partially and simultaneously, as perceived by the department heads.Methods – This study employed a quantitative research approach using multiple linear regression analysis. The sample consisted of 30 vocational high school department heads selected through purposive sampling. Data were collected using a structured questionnaire that measured the PDIA approach, leadership style, and observations of student discipline. The instrument was validated for content and construct, with reliability established using Cronbach’s Alpha to ensure measurement consistency. Findings – The results indicate that the PDIA approach has a positive and significant effect on students’ discipline culture. Department head leadership also shows a positive and significant influence. Simultaneously, both variables significantly contribute to discipline culture, with an R-squared value of 0.9729. While this high value suggests a strong predictive model within the sample, it is interpreted with caution regarding potential construct overlap or common method bias due to the single-source perceptual data. Research Implications – These findings imply that strengthening the implementation of the PDIA approach and enhancing adaptive academic leadership are essential strategies for improving discipline culture. However, future studies are recommended to use multi-source data (e.g., combining student and teacher reports) to validate these findings and reduce potential measurement bias.